Principal's Strategy in Improving Teacher Performance in Islamic Education Learning - Misdah Misdah (AT-TURATS, 2020)
The purpose of this study was to find out about (1) the principal's strategy in improving teacher performance in PAI learning planning; (2) the principal's strategy in improving teacher performance in the implementation of PAI learning; and (3) the principal's strategy in improving teacher performance in pai learning evaluation. This type of research is field research(fiel research),while the approach used is qualitative approach. Data collection techniques used are observation, interview and documentation studies. The data sources in this study are 1 principal and 2 PAI teachers located at SMP Muhammadiyah 1 Pontianak. The results of this study show that: (1) the principal's strategy in improving teacher performance in PAI learning planning, is to provide skills, motivation and conduct academic supervision for learning planning at the beginning of the year; (2) The principal's strategy in improving teacher performance in the implementation of PAI learning is to conduct academic monitoring and supervision in the form of regular class visits to each teacher and directly supervise the teacher in carrying out learning stages such as: preliminary activities, core activities and closing activities; and (3) the principal's strategy in improving teacher performance in pai learning evaluation is also by conducting academic supervision in the form of classroom visits and directly monitoring teachers in providing feedback as a result of the evaluation process provided by teachers in the classroom